Investigation of hexanal removal through adsorption and photocatalysis on ZIF-7 modified with ZnO, TiO\(_2\), and ZnO/TiO\(_2\) using ATR-FTIR - Naufal, Widyan Muhammad; Wahyuningsih, Sayekti; Lestari, Witri Wahyu (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2024)
Zeolitic imidazolate framework (ZIF) is renowned for its high adsorption capacity and frequently adsorbs organic pollutants. However, its high band gap energy has limited its photocatalytic activity, thus necessitating a modification for enhance performance enhancement. This study focuses on developing a ZIF-7 composite material that integrates adsorption and photocatalysis to remove volatile organic compounds (VOCs), particularly hexanal. Modifications were made by incorporating ZnO, TiO2, and ZnO/TiO2 via a solvothermal method using dimethylformamide (DMF). ATR-FTIR analysis was employed to monitor any changes in peak intensity related to the C=O vibrations of hexanal around 1700 cm-1. The results showed that all samples effectively adsorbed hexanal, reducing peak intensity after UV irradiation, and confirming successful photocatalysis. Notably, TiO2@ZIF-7 exhibited the highest photocatalytic performance with 88.06% degradation efficiency. This study confirms that the ATR-FTIR method can be used to monitor the success of adsorption and photocatalysis and shows the potential for developing composite materials to remove VOCs such as hexanal.